Outward FDI and home country employment - Chen, Jen Eem; Chin, Lee; Law, Siong Hook; Wan Ngah, Wan Azman Saini (International Academic Research, 2016)
TThis paper aims to explore the effects of Malaysian outward FDI on its home country employment, specifically skilled and unskilled employments. We use annual data spans from 1980 to 2012 that is examined in autoregressive distributed lag (ARDL) bounds testing framework. The findings reveal that national output is positively associated with both skilled and unskilled employments. Interest rate is found to have negative relationship with skilled labour that reflects complementary inputs between labour and capital. The positive and significant relationship between interest rate and unskilled labour indicates the existence of substitution relationship between them. However, we found no empirical evidence showing that outward FDI has a significant impact on skill composition.